Antifungal activities and mechanisms of trans‐cinnamaldehyde and thymol against food‐spoilage yeast Zygosaccharomyces rouxii. Issue 3 (12th February 2022) - Wang, Huxuan; Peng, Zhonghua; Sun, Hongmin
Abstract : Abstract: Due to hydrophobicity, plant essential oil components trans ‐cinnamaldehyde and thymol exert broad‐spectrum antimicrobial activities by interfering with the structures and functions of microbial cell membranes, yet their antifungal properties against food‐spoilage yeast Zygosaccharomyces rouxii are still unclear. This work aimed to elucidate their antifungal activities and mechanisms against Z. rouxii . Minimum inhibitory concentration (MIC) and minimum fungicidal concentration (MFC) were measured using broth dilution method to evaluate the antifungal activities. Membrane permeability, potential and integrity, intracellular ATP content, and intracellular pH (pHin ) were determined, and membrane damage was observed by scanning electron microscope (SEM) to investigate the antifungal mechanisms. The MICs of trans ‐cinnamaldehyde and thymol were 0.3125 and 0.0625 mg/ml, respectively, and the MFCs were 1.25 and 0.125 mg/ml, respectively. Increased membrane permeability, membrane hyperpolarization, decreased membrane integrity, reduced intracellular ATP content, and lowered pHin were found after trans ‐cinnamaldehyde or thymol treatment at the MIC and MFC levels, and thymol exhibited more severe influence on cell membrane. SEM observation further confirmed that trans ‐cinnamaldehyde caused cell membrane shrinkage and invagination, while thymol resulted in perforation in cell membrane. These results suggest that trans ‐cinnamaldehyde and thymol exert anti‐ Z. rouxii activities by inducing cell membrane damage and subsequent intracellular homeostasis disruption. Cellular contents leakage and intracellular homeostasis disruption probably proceed more rapidly after thymol inducing perforation in the cell surface, thereby thymol exerting better anti‐ Z. rouxii activity. Practical Application: The addition of a small amount of thymol (0.125 mg/ml) is sufficient to effectively inhibit the growth of Z. rouxii in apple juice concentrate. Based on our previous work, the addition of thymol (0.125 mg/ml) in apple juice concentrate did not significantly affect the organoleptic property of the diluted apple juice (5°Brix) used for producing commercial apple juice products. Therefore, thymol is practical for application at the effective concentration (0.125 mg/ml) in apple juice concentrate.